Estimating time-varying coefficients with Gretl using the VC method - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2022)
This paper documents the function and use of the Gretl function package VCwrapper.pdf that implements the VC method for estimating time-varying coefficients in linear models as described in Schlicht (2021). It builds on the VCC program by Schlicht (2021a), is easy to use and highly configurable. It runs under Windows and Linux.
urn:nbn:de:bvb:19-epub-84611-4
Keywords: C22; 330; Kalman filtering; Kalman-Bucy; random walk; time-varying coefficients; adaptive estimation; time-series; Gretl